2012
DOI: 10.1016/j.bbalip.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The “beta-clasp” model of apolipoprotein A-I — A lipid-free solution structure determined by electron paramagnetic resonance spectroscopy

Abstract: Apolipoprotein A-I (apoA-I) is the major protein component of high density lipoproteins (HDL) and plays a central role in cholesterol metabolism. The lipid-free / lipid-poor form of apoA-I is the preferred substrate for the ATP-binding cassette transporter A1 (ABCA1). The interaction of apoA-I with ABCA1 leads to the formation of cholesterol laden high density lipoprotein (HDL) particles, a key step in reverse cholesterol transport and the maintenance of cholesterol homeostasis. Knowledge of the structure of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 73 publications
6
74
0
1
Order By: Relevance
“…have been experimentally found to have higher propensity for lipid binding. 11,22,25,[37][38][39][40] Our simulations are in excellent match with all these previous results and shows new regions of lipid-binding initiation in concentration gradient manner.…”
Section: 31supporting
confidence: 85%
“…have been experimentally found to have higher propensity for lipid binding. 11,22,25,[37][38][39][40] Our simulations are in excellent match with all these previous results and shows new regions of lipid-binding initiation in concentration gradient manner.…”
Section: 31supporting
confidence: 85%
“…DMEM, H6(AB), H7(AB), H8(BB), H9(B), and H10(AB) (10). Sequence analysis (9,10), NMR assignments (11), hydrogen-deuterium exchange measurements (12,13), and site-directed spin-label electron paramagnetic resonance spectroscopy (14)(15)(16)(17) have provided different distributions, flexible regions, and positions for these putative helical tandem repeats in lipid-free or lipid-bound state. In addition, segment deletion and point mutation studies have further elucidated the possible conformation and function for each helical segment (18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%
“…15 The APOL1 concentrations in media to which our cell lines were exposed were far lower than those previously reported by Duchateau in serum (5-10 mg/ml) 16 and estimated in our studies (15 mg/ml). Assuming that #5% of serum APOL1 exists in a lipid-free form, as is the case for APOA1, 17,18 we estimate that approximately 0.75 mg/ml APOL1 could potentially cross the glomerular filtration barrier. This concentration is within the range used in our in vitro study, where we observed significant uptake of APOL1 by podocytes (Figure 8, Supplemental Figures 3, 5-7), but not by endothelial and mesangial cells, and is consistent with the observed enrichment of podocyte APOL1 signal in kidney cryosections.…”
Section: Discussionmentioning
confidence: 99%